Short Communication: Abundance of Arbuscular Mycorrhiza asociated with corn planted with traditional and more modern farming systems in Kupang, East Nusa Tenggara, Indonesia - LILY ISHAQ; ANTHONIUS S.J. ADU TAE; MORESI A. AIRTHUR; PETERS O. BAKO (Society for Indonesian Biodiversity, 2017)
Abstract. Ishaq L, Adu Tae ASJ, Airthur MA, Bako PO. 2017. Short Communication: Abundance of Arbuscular Mycorrhizal Fungal spores associated with corn planted with traditional and more modern farming systems at East Nusa Tenggara, Indonesia. Biodiversitas 18: 887-892. Mycorrhizal fungi play an important role in improving plant productivity and soil conservation. One factor that may have an impact on the population of mycorrhizal fungi in the soil is the land management. The study aimed to investigate the impact of land management on the spore density of arbuscular mycorrhiza (AM) associated with corn, and was undertaken at 6 sites in Kupang District of East Nusa Tenggara Province, Indonesia Two farming systems (traditional and more modern) were chosen for the study, and three locations were selected to represent each farming system practiced. Representative soil samples were taken from each location/farming system for AM observation and soil analysis. The results showed that spore density of AM fungi was higher in soil taken from corn plantation with traditional practice than that found in soil taken from corn plantation with more modern practice, indicating a negative impact of the more modern farming practice on the population of AM fungi. The research should be extended to further investigate the diversity and communities of AM fungi at different time and location.